"Time is Brain"—How early should surgery be done in drug‐resistant TLE?. (21st August 2018) - Radhakrishnan, Ashalatha; Menon, Ramshekhar; Thomas, Sanjeev V.; Abraham, Mathew; Vilanilam, George; Kesavadas, Chandrashekharan; Thomas, Bejoy; Cherian, Ajith; Varma, Ravi Prasad
Abstract : Objectives: To explore the effect of duration of epilepsy and delay in surgery on seizure outcome in patients operated for drug‐resistant temporal lobe epilepsy (TLE). Materials & methods: A total of 664 consecutive patients who underwent anterior temporal lobectomy (ATL) for TLE from 1995 to 2008 formed the study cohort. We divided them into two, one as seizure‐free with or without antiepileptic drugs after ATL as "good outcome" (Engel class I a) and seizures of any type, any time after surgery as "poor outcome." The probability of seizure freedom/seizure recurrence based on the duration of epilepsy was compared using Kaplan‐Meier curves, univariate Cox regression survival analysis, and multivariate Cox proportional hazards regression model. Results: A total of 136 children and 528 adults underwent ATL during this period. Mean duration of epilepsy pre‐ATL was 17.1 +  9.4 years. At mean follow‐up of 8.5 years, 331 patients (49.8%) had good outcome and 333 (50.2%) had poor outcome. The hazard of seizure recurrence linearly increased with duration of epilepsy pre‐ATL, from 1.5 (duration of epilepsy, 5‐10 years) to 1.9 (duration of epilepsy, 10‐15 years) to 2 (duration of epilepsy over 15 years). In addition, encephalitis as antecedent, bilateral mesial temporal sclerosis in MRI, normal histopathology, and spikes in postoperative EEG at 3 months and 1 year predicted poor seizure outcome. Conclusions: "Epilepsy duration" independently predicted both short‐ and long‐term seizure outcome after surgery in TLE. "Lost years" translate into poor seizure outcome after ATL. Therefore, all cases of drug‐resistant TLE should be referred to a surgical center at the earliest.